Agrimonia pilosa: A Phytochemical and Pharmacological Review. (29th April 2022) - Jin, Tianyu; Chi, Li; Ma, Chongyang
Abstract : Agrimonia pilosa Ledeb., which belongs to Agrimonia and Rosaceae, is used in traditional Chinese medicine. It exhibits excellent medicinal properties and has been used to treat various diseases, such as tumors, trichomoniasis, vaginitis, diarrhea, and dysentery. Phytochemical studies have revealed that Agrimonia has over 100 secondary metabolites that can be categorized into six classes, i.e., flavonoids, isocoumarins, triterpenes, phloroglucinol derivatives, tannins, and organic acids. This review summarizes recently published literature on the chemical structures of 90 bioactive compounds that have been identified in A. pilosa and examines their pharmacological properties, including their antitumor, anti-inflammatory, antioxidant, antibacterial, and antidiabetic properties, as well as the potential development of parasitic resistance to these chemicals. This review highlights existing knowledge gap and serves as a basis for developing novel preparations of A. pilosa with medicinal value.